Content - 33, VOX JURIS (2017)
Neurocriminology as an emerging applied disciplineFacial identification of emotions: utility in bodies and security forces (local police).The granting (or refusal) of parole: the development of interlocutory decisions. A case study in Argentina.This is also a prison, although more in a therapeutic sense: practices, discourses and thoughts from the prison world in regards to the SPF psychiatric services.The implications of punishment. An ethnographic study in a women´s prison in Argentina.The persecution of poverty: the judicial power as a protagonic subject in the construction of the others.The citizen the refugee in Agamben´s work.Howard Becker: the contemporary of the Chicago School? The theory of labeling in the process of criminalization.Towards contenmporary criminologySymbolic ineffective criminal law and state constitutional emergency to fight crimeThe criminal law as